2013
DOI: 10.1016/j.tet.2013.05.060
|View full text |Cite
|
Sign up to set email alerts
|

Template-induced macrocycle diversity through large ring-forming alkylations of tryptophan

Abstract: Macrocyclic peptidomimetics are valuable in research and serve as lead compounds in drug discovery efforts. New methods to prepare such structures are of considerable interest. In this pilot study, we show that an organic template harboring a latent cinnamyl cation participates in novel Friedel-Crafts macrocyclization reactions with tryptophan. Upon joining the template to Trp-Trp-Tyr, a single operation efficiently generates eight unique macrocycles. Each has been isolated and thoroughly characterized. Produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 100 publications
0
27
0
Order By: Relevance
“… 8 To our knowledge, synthesis of macrocyclic pyrroloindolines by intramolecular indole C3 substitution is limited to one example in an initial communication by us ( vide infra ). 9 The present study accesses six new products bearing these motifs, as well as thirty-nine additional indolic macrocycle isomers, and characterizes their structures and reactivity in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 To our knowledge, synthesis of macrocyclic pyrroloindolines by intramolecular indole C3 substitution is limited to one example in an initial communication by us ( vide infra ). 9 The present study accesses six new products bearing these motifs, as well as thirty-nine additional indolic macrocycle isomers, and characterizes their structures and reactivity in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study of internal alkylations of tryptophan-containing peptides, we characterized the products derived from acidolysis of composite oligomer 2 ( Scheme 1 ). 9 When treated with Brønsted or Lewis acid, degradation of the cinnamyl carbonate in 2 led to competing internal Friedel–Crafts alkylations of proximal tryptophan and tyrosine side chains. The distribution of products was sensitive to acid promoter, solvent and temperature.…”
Section: Introductionmentioning
confidence: 99%
“… 28 Notable recent examples come from the research groups of Wessjohann, 28 , 29 Marcaurelle, 30 Marsault 9 and Harran. 31 Overall however, there still remains a relative lack of DOS strategies that are specifically directed towards macrocyclic peptidomimetics. Reports beyond the proof-of-principle stage (that is, involving the application of such DOS strategies for the generation of large numbers of structurally diverse compounds based around a variety of macrocyclic peptidomimetic ring architectures) are rare.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that decomposition of a cinnamyl carbonate within the template could capture pendant tyrosine residues to form cyclic ethers (51,54). This result followed from catalysis pioneered by Tsuji and Trost.…”
mentioning
confidence: 97%